Label-free, live optical imaging of reprogrammed bipolar disorder patient-derived cells reveals a functional correlate of lithium responsiveness - Wang, J L; Shamah, S M; Sun, A X; Waldman, I D; Haggarty, S J; Perlis, R H (Translational psychiatry, 2014)
Development of novel treatments and diagnostic tools for psychiatric illness has been hindered by the absence of cellular models of disease. With the advent of cellular reprogramming, it may be possible to recapitulate the disease biology of psychiatric disorders using patient skin cells transdifferentiated to neurons. However, efficiently identifying and characterizing relevant neuronal phenotypes in the absence of well-defined pathophysiology remains a challenge. In this study, we collected fibroblast samples from patients with bipolar 1 disorder, characterized by their lithium response ( n =12), and healthy control subjects ( n =6). We identified a cellular phenotype in reprogrammed neurons using a label-free imaging assay based on a nanostructured photonic crystal biosensor and found that an optical measure of cell adhesion was associated with clinical response to lithium treatment. This cellular phenotype may represent a useful biomarker to evaluate drug response and screen for novel therapeutics.